Views of university students in Jordan towards Biobanking - Faisal Khatib (BMC, 2021)
Abstract Background Biobanks are considered primary means+ of supporting contemporary research, in order to deliver personalized and precise diagnostics with public acceptance and participation as a cornerstone for their success. Aims This study aims to assess knowledge, perception, and attitudes towards biomedical research and biobanking among students at the University of Jordan. Methodology An online questionnaire was designed, developed, and piloted. It was divided into 5 sections that included questions related to issues of biomedical research and biobanking as well as factors influencing the decision to participate. Results Responses from 435 students revealed that 52.9% previously heard of biobanks. There was an overwhelming acceptance for participation in biomedical, genetic, and biobanking research. A blood sample was the most preferred for donation. Protection of privacy, informed consent prior to donation, approval of an ethics committee, and trust towards researchers were the most important factors associated with willingness to participate. On the other hand, the vagueness of the type of research performed on the biospecimens and the unavailability of general research results to the donor had a negative connotation. There was no clear agreement on the type of informed consent preferred by students, but to be contacted and informed of research results was preferred by the majority. Students also preferred the disposal of biospecimens and information when deciding to withdraw from participation. Conclusion There is strong enthusiasm among students to participate in biomedical research and biobanking with all rights reserved thus providing hope for a very promising future in Jordan.